Empowering urban agriculture: a sustainable model of aquaponic waqf - Mohamad Isa Abd Jalil; Suddin Lada; Siti Hajar Samsu; Rudy Ansar; Brahim Chekima; Anwar Allah Pitchay; Hasliza Talib (Labuan Faculty of International Finance, Universiti Malaysia Sabah, 2024)
This conceptual paper introduces a waqf model for an aquaponic system aimed at enhancing food security for urban residents, particularly those in flats or apartment housing in Malaysia, which still relies on foreign countries for key food commodities like rice, fruits, dairy, and beef. The proposed model, designed to be simple and adaptable, is in its initial stages and requires validation by experts in Islamic finance and food security. The study outlines the purpose of creating a base model that can be improved and customized to meet various needs, with the hope that it will significantly impact food security practices through waqf. However, the model's current limitation is its conceptual nature, necessitating further development and validation. The novelty of this approach lies in its integration of aquaponics and waqf to address urban food security challenges.